Butyrate and hexanoate-enriched triglycerides increase postprandrial systemic butyrate and hexanoate in men with overweight/obesity: A double-blind placebo-controlled randomized crossover trial - van Deuren, Thirza; Smolders, Lotte; Hartog, Anita; Bouwman, Freek G.; Holst, Jens J.; Venema, Koen; Blaak, Ellen E.; Canfora, Emanuel E. (Frontiers in Nutrition, 2023)
Background: Short chain fatty acids (SCFA) are increasingly recognized for their potential ability to alleviate obesity-associated chronic low-grade inflammation and disturbed energy homeostasis. Evidence suggests that an increase in circulating SCFA might be necessary to induce beneficial alterations in energy metabolism. Objective: To compare the bioaccessibility of two different SCFA-enriched triglycerides: Akovita SCT (butyrate and hexanoate esterified with long chain fatty acids) and tributyrin/caproin (solely butyrate and hexanoate) and investigate whether the SCFA from orally administrated Akovita SCT reach the circulation and affect postprandial metabolism in men with overweight/obesity. Methods: The site, speed, and amount of SCFA release from Akovita SCT and tributyrin/caproin were assessed in a validated In vitro Model of the stomach and small intestine (TIM-1). Subsequently, a double-blind placebo-controlled randomized crossover study was conducted at Maastricht University with fourteen men with overweight/obesity (BMI 25-35 kg/m2) of which 12 men finished all testdays and were included for analysis. The participants received a liquid high fat mixed meal test containing either a low (650 mg), medium (1325 mg), or high dose (2000 mg) of Akovita SCT or a placebo (sunflower oil) in randomized order. Blood was sampled at baseline and after ingestion for 6h for the primary outcome plasma butyrate and hexanoate concentration. Secondary outcomes included hydrogen breath, appetite, gastrointestinal complaints, circulating glucagon-like peptide 1, free fatty acids, glucose, triglycerides, insulin, and cytokines concentrations. Results: In TIM-1, tributyrin/caproin was rapidly cleaved in the gastric compartment whereas the release of SCFA from Akovita SCT occurred predominantly in the small intestine. In vivo, all doses were well tolerated. The medium dose increased (P<0.05) and the high dose tended to increase (P<0.10) postprandial circulating butyrate and both doses increased circulating hexanoate (P<0.05) compared to placebo. Nevertheless, Akovita SCT supplementation did not affect any secondary outcomes compared to placebo. Conclusion: Esterifying SCFA-enriched triglycerides with long chain fatty acids delayed SCFA release from the glycerol backbone. Akovita SCT increased postprandial circulating butyrate and hexanoate without changing metabolic parameters in men with overweight/obesity. Future randomized clinical trials should investigate whether long-term Akovita SCT supplementation can aid in the treatment or prevention of metabolic disorders.